In Vitro Antiplasmodial, Cytotoxicity, and Antioxidant Activities of Lophira lanceolata (Ochnaceae): A Cameroonian Plant Commonly Used to Treat Malaria - Mounvera Abdel Azizi; Noumedem Anangmo Christelle Nadia; Yamssi Cedric; Gamago Nkadeu Guy-Armand; Ngouyamsa Nsapkain Aboubakar Sidiki; Tientcheu Noutong Jemimah Sandra; Tako Djimefo Alex Kevin; Vincent Khan Payne (Journal of Tropical Medicine)
Background. Malaria is the leading cause of morbidity and mortality in African countries. We aimed this study at evaluating the in vitro antiplasmodial, antioxidant, and cytotoxicity activity of Lophira lanceolata extracts. Method. The aqueous and ethanol extracts were obtained by maceration. It tested in vitro the extracts against Plasmodium falciparum 3D7 and multiresistance Dd2. Macrophage cell lines (RAW 264.7 cells) and red blood cells were used for cytotoxicity tests. The antioxidant activity was assessed by 1,1-diphenyl-2-picrylhydrazine (DPPH), hydrogen peroxide (H2O2), nitric oxide (NO) reduction, and ferric reducing antioxidant power (FRAP) scavenging. Results. The in vitro antiplasmodial results showed that the ethanol extract was the most active, with IC50 of 24.51 ± 4.77 µg/mL and 31.86 ± 3.10 µg/mL, respectively, on the resistant Dd2 and sensitive 3D7 strains unlike the aqueous which indicated moderate activity with an IC50 of 51.36 ± 4.86 μg/mL and 56.36 ± 4.27 μg/mL, respectively, on the resistant Dd2 and sensitive (3D7) strains. However, the ethanol extract had the highest activity, with an IC50 of 8.153 g/mL, 1915 g/mL, 30.81 g/mL, and 54.66 g/mL, respectively, for DPPH, H2O2, NO, and FRAP, while the aqueous extract had an IC50 of 6.724, 2387681, 185.7, and 152.0 g/mL, respectively, for DPPH, H2O2, NO, and FRAP. The cytotoxicity test reveals that both extracts do not promote red blood cell haemolysis. They presented weak activity against RAW 264.7 cells and red blood cells. Conclusion. According to these findings, the aqueous and ethanol extracts have antiplasmodial and antioxidant activity but with no cytotoxic effects on red blood cells or RAW cells. However, it will be important to investigate the in vivo antiplasmodial and antioxidant activity of these extracts.